Potential role of frugivorous birds (Passeriformes) on seed dispersal of six plant species in a restinga habitat, southeastern Brazil - Verônica Souza da Mota Gomes; Maria Célia Rodrigues Correia; Heloisa Alves de Lima; Maria Alice S. Alves (Revista de Biología Tropical, 2008)
Restingas are considered stressful habitats associated with the Brazilian Atlantic forest, and their ecological interactions are poorly known. The goal of the present study was to determine the potential role of frugivorous birds as seed dispersers in a restinga habitat. Data were collected in Parque Nacional da Restinga de Jurubatiba, southeastern Brazil, where the main physiognomy (Open Clusia Formation) is characterized by the presence of patches of vegetation covering 20 to 48 % of the sandy soil and reaching a height of 5 m. Birds were captured with mist nets (12 x 2.5 m; 36 mm mesh; 1 680 net-hrs) and had their fecal and regurgitate samples inspected for seeds. Six plant species found in these bird samples were studied. The germination of seeds obtained from plants was compared to those from the birds. Both groups of seeds were set on Petri dishes at room temperature and washed when infected with fungi. In general, there was no effect on germination rate, and the effect on germination speed was negative. Germination of seeds from Pilosocereus arrabidae treated by the birds seemed to be influenced by storage of defecated seeds, while few Miconia cinnamomifolia seeds both from plants and from birds germinated. Ocotea notata presented a great variation in time to the onset of germination, perhaps an advantage against dissecation. Aechmea nudicaulis, Clusia hilariana and Erythroxylum subsessile probably take advantage of the arrival to favorable microhabitats, not by the gut effect on the seeds. All plant species studied are numerically important for the community and some of them are main actors in the succession of vegetation patches. Among the birds, Mimus gilvus is an important resident species, endemic to restingas in Brazil, while Turdus amaurochalinus is a visitor and may be important for plants that fructify during its passage by the study site. Although the effect of pulp removal was only tested for one species (Achmea nudicaulis) in the present study, we confirmed that the tested effect of restinga frugivorous birds on seed germination was generally null. Although there is a need for more detailed studies on specific animal-plant interactions on this habitat, the overall effect of the birds on seed dispersal in restinga is probably positive. Rev. Biol. Trop. 56 (1): 205-216. Epub 2008 March 31. Las restingas se consideran hábitats estresantes asociados al bosque del Atlántico brasileño y sus ecológicas se conocen poco. El objetivo principal del presente trabajo fue determinar el papel potencial de las aves frugívoras como dispersores de plantas en un hábitat de restinga. La información se recolectó en el Parque Nacional da Restinga de Jurubatiba, Brasil. Las aves se capturaron con redes de niebla y sus muestras fecales y de regurgitación se inspeccionaron en busca de semillas. Estudiamos seis especies de plantas de estas muestras. En general, el efecto del paso por el sistema digestivo de las aves sobre el porcentaje de germinación fue nulo (y negativo en la velocidad de germinación). Todas las especies de plantas estudiadas son numéricamente importantes a la comunidad y algunas de ellas tienen papeles principales en la sucesión de parches de vegetación. Entre las aves, Mimus gilvus es una especie residente importante, endémica de tales hábitats en Brasil, mientras que Turdus amaurochalinus es una especie visitante y puede ser importante para las plantas que fructifican durante su paso por el sitio del estudio. El efecto general de los pájaros en la dispersión de semillas en la restinga es probablemente positivo.